Dating high temperature metamorphic rocks: a case study of isotopic and trace element complexity in zircon and monazite from South India - Meier, Vicky Lara (Curtin University, 2016)
Metasedimentary rocks from the Trivandrum Block and Achankovil Zone in South India have been used to study zircon and monazite behaviour during high-temperature metamorphism. Isotopic and chemical data from these accessory minerals reveal that metamorphism had begun before $\sim$600 Ma and was waning by $\sim$510 Ma, but widespread disruption of this isotopic record by differential lead-loss and contamination with reset inherited grains make it difficult to date specific stages within this prolonged orogenic history.